Evaluasi Penerapan Agile dalam Pengembangan Inventory Management System Berbasis Web dengan Dashboard Real‑Time - Hidayat, Rahmat; Afriansyah, Afriansyah; Al Farasy Syam, Febrizal; Turnades, Yogo; Vebby, Vebby (Riau Jurnal Teknik Informatika, 2025)
Inventory data management at PT Maksindo Pekanbaru is still performed manually using Microsoft Excel, leading to several issues such as input errors, data redundancy, limited real-time stock monitoring, and a high dependence on paper-based documentation. These conditions negatively impact operational efficiency and reporting accuracy. This study aims to develop and evaluate a web-based inventory management system equipped with a real-time dashboard using the Agile Software Development approach. Agile was selected for its ability to accommodate changing user requirements through iterative and collaborative development cycles. The system was developed through multiple sprints, encompassing planning, design, implementation, testing, and evaluation phases. The evaluation results indicate that the system improves the efficiency of data recording processes, reduces paper usage, and provides more informative data visualization through a real-time dashboard. These findings suggest that the implementation of the Agile method is effective in supporting the development of adaptive information systems that respond well to evolving user needs and operational environments. Keywords: Agile, inventory management system, web-based system, real-time dashboard, system evaluation